Good governance practices for sustainable development in the public sector services in Malaysia - Zabidi, Nadirah; Ismail, Mohd Mahadee; Adnan, Zatul Himmah; Mohd Zain, Mohd Izani (2024)
Good governance is indicated as the remedy that results in political stability and a key basis towards sustainable growth and development that can facilitate the institution’s effectiveness and efficiency. Malaysia has been seen to be practising good governance in the public institutions through the holistic reform agenda that requires the highest quality of ethics and conduct for every level that aims to strengthen transparency and increase accountability throughout administrative activities. Therefore, this paper seeks to uncover the status of good governance for sustainable development in public administration in Malaysia. In this paper, studies from literature reviews and reports from the Economic Planning Unit, Malaysia Plan, and Public Service Ethics are used as a research method to describe the status of good governance for sustainable development in Malaysia. This practice of good governance is noticeable in most of the plans and policies that already assist public institutions in enhancing their quality and performance for delivering services for the citizen. However, the criticisms towards the public sector services remain to be heard, and this process of enhancing the quality and performance is challenging. This is why the holistic reform plan is considered the dawn for Malaysia in routing towards good governance for sustainable development.